EEG And Reg Indicators In Workers With Varying Degrees Of Professional Hearing Loss - Nasretdinova M.T. (Genius Journals, 2024)
The auditory zone of the cerebral cortex is the first to react to noise exposure, giving rise to subsequent changes in other parts of the sound analyzer. Clinical and experimental observations also indicate a close relationship between disorders of cerebral hemodynamics and bioelectric activity of the brain in various diseases
Keywords: Noise Exposure; Electroencephalography; Photostimulation